2014
DOI: 10.1038/hr.2014.124
|View full text |Cite
|
Sign up to set email alerts
|

Association between single-nucleotide polymorphisms in six hypertensive candidate genes and hypertension among northern Han Chinese individuals

Abstract: Hypertension is one of the leading risk factors for mortality. The renin-angiotensin-aldosterone system (RAAS) is a potent and powerful mediator in the homeostasis of hypertension. Here, the association between six candidate genes, renin, adrenoceptor β3, angiotensinogen, aldosterone synthase, angiotensin II receptor type 1 and angiotensin II receptor type 2, that are related to RAAS and essential hypertension (EH) was evaluated and explored in northern Chinese Han individuals. A case-control study including 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
3
15
0
1
Order By: Relevance
“…Similar data were obtained by Wang et al, who studied this polymorphism and reported no association with hypertension in Han Chinese population (Wang et al, 2014). In contrast with these data, the rs5707 polymorphism has been associated with increased risk of developing hypertension and acute pancreatitis in European populations (Mansego et al, 2008;Skipworth et al, 2015).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar data were obtained by Wang et al, who studied this polymorphism and reported no association with hypertension in Han Chinese population (Wang et al, 2014). In contrast with these data, the rs5707 polymorphism has been associated with increased risk of developing hypertension and acute pancreatitis in European populations (Mansego et al, 2008;Skipworth et al, 2015).…”
Section: Discussionsupporting
confidence: 72%
“…Polymorphisms in the genes that encode these molecules have been associated with risk of developing inflammatory diseases, such hypertension, atherosclerosis, vascular disease, coronary artery disease, blood pressure, coronary artery bypass graft, preeclampsia, and acute pancreatitis (Mansego et al, 2008;Ragia et al, 2010;Dzielinska et al, 2011;Abd El-Aziz et al, 2012;Al-Najai et al, 2013;Brugts et al, 2011;Wang et al, 2014;Skipworth et al, 2015;Mirsha et al, 2012). In the present work, we studied seven polymorphisms, five located in the AGT gene and two located in the REN gene.…”
Section: Discussionmentioning
confidence: 95%
“…Rs4994, a polymorphism in ADRB3, has been evaluated in hypertensive studies. This variant is associated with essential hypertension in Han Chinese 64 , mean thiazide BP response in Japanese individuals 65 , and pulse pressure variation between atenolol and losartan in whites 17 . These associations were not corrected for a multiple testing penalty and have not been replicated.…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…In a study investigating the effect of Arg16Gly, Gln27Glu and Trp64Arg polymorphisms on weight loss among adult obese (n = 109) women in Brazil, a seven-week dietary and physical activity intervention did not result in significant differences in weight loss between polymorphisms carriers and non-carriers [39]. Interestingly, the presence of the Arg64 allele in the ADRB3 gene was associated with lower BMI and high density lipoprotein cholesterol levels in individuals with T2DM in Brazil [40], and the Arg64 allele was negatively associated with HTN in a population of approximately 1800 in China [41]. Results from the DiOGenes (Diet, Obesity and Genes) study on European populations revealed that the presence of G allele of rs4998 in the ADRB3 gene enhanced the effect of waist circumference reduction of high-protein diets [42].…”
Section: Beta-adrenergic Receptors: Adrb2 and Adrb3 Genesmentioning
confidence: 95%